Evaluating the Correlation between the Teaching Performance of Primary School English Language Teachers and the Training they Received - Melese Beshah; Alemu Hailu Anshu (Educational Challenges)
Teaching is a profession that requires its practitioners to be trained and certified. The training may take the form of pre-service or in-service. The teachers who pass through either of these modes of training are also required to possess ample and reasonable knowledge and skills of the subject matter they teach. In addition, the training that they take should focus on shaping their attitudes towards the teaching profession so that they can adapt, improve or change the reality they find in schools. In addition, they are expected to possess ample experiences of teaching.